The Effect of Nira Beverage Consumption on Blood Glucose Levels and Glycemic Index in Patients with Diabetes Mellitus: An Experimental Study - Liawaty Usman Sidiki; Sunarto Kadir; Laksmyn Kadir (Indonesian Journal of Global Health Research, 2026)
Diabetes mellitus (DM) is a major public health problem with a continuously increasing prevalence. Dietary regulation is a key pillar in glycemic control for DM management. Palm sap (nira aren) is a traditional beverage reported to have a low glycemic index; however, public concerns regarding its potential alcohol content have raised controversy about its consumption among individuals with DM. This study aimed to determine the effect of nira beverage consumption on blood glucose levels and glycemic index in patients with diabetes mellitus. This study employed a quasi-experimental pretest–posttest control group design involving 28 patients with diabetes mellitus. Data were collected through direct measurement of blood glucose levels using a glucometer before and after the intervention, while glycemic index was calculated based on standardized glycemic response procedures. Statistical analysis was performed using the paired t-test. The findings showed a statistically significant difference in blood glucose levels before and after nira beverage consumption in the intervention group (p = 0.000). In addition, glycemic index analysis demonstrated a significant difference (p = 0.001). Nira beverage consumption has a significant effect on blood glucose levels and glycemic index among patients with diabetes mellitus.